The Influence of Analysis Mode Selection on Prediction Accuracy of Corneal Astigmatism Using Pentacam - Meng, Jiaqi; Yu, Jifeng; He, Wenwen; Wei, Ling; Lu, Yi; Zhu, Xiangjia (Frontiers in Medicine, 2021)
Purpose: To evaluate the influence of analysis mode selection on prediction accuracy of corneal astigmatism using Pentacam. Methods: Fifty-nine eyes of 59 patients implanted with toric intraocular lenses (IOLs) were included in the retrospective study. Preoperative corneal astigmatism (total refractive power) measured with Pentacam were analyzed based on 2-, 3-, 4-, or 5mm ring or zone mode either centered on corneal apex or pupil center. Actual corneal astigmatism was calculated based on residual astigmatism on corneal plane, surgical induced astigmatism and effective toric power on corneal plane. Prediction error, the difference between actual corneal astigmatism and measured astigmatism, was compared among different analysis modes. Influences of local topography on prediction error was also evaluated. Results: Based on the zone mode, prediction error was lower when centered on corneal apex than on pupil center at different diameters, whereas based on the ring mode, this difference was only seen at 2mm cornea (all P<0.05). When centered on corneal apex, the zone mode showed lower prediction error than the ring mode at 4- and 5mm cornea (both P<0.001), regardless of asymmetric or symmetric astigmatism. In symmetric bowtie, the zone mode showed lower prediction error than the ring mode at 2mm cornea of small bowtie, and 4- and 5mm cornea of large bowtie (all P<0.05). Conclusions: For toric IOL planning, corneal apex may be a better reference center. At cornea diameter ≥ 4mm, the zone mode is more accurate than the ring mode. Local topography affects prediction accuracy in symmetric bowtie.